Pupils' Attitudes toward Inclusive Education - Strnadová, Anna; Potmesil, Milon; Potmesilova, Petra (Children, 2023)
The presented research is a study of the attitudes of adolescents toward individuals with disabilities and a description of the level of knowledge about this issue among a selected group of adolescents. The study is focused on the school social environment, specifically on pupils without disabilities and their attitudes toward pupils with disabilities, which is one of the factors influencing their school success. The target group was 1806 pupils between the ages of 11 and 16 from the entire Czech Republic, approached by random selection. The research tool for the quantitative approach was a questionnaire developed by the authors of this article. The questionnaire section with open questions served for the qualitative part of the research. The results show that 70% of the respondents have basic knowledge about people with disabilities. Furthermore, it was shown that these adolescents have an overall positive attitude toward people with disabilities. This attitude is statistically significantly better among the girls than the boys, and the girls are also more open to discussing individuals with disabilities. At the same time, even if attitudes are positive, they still depend on the type of disability. The greatest uncertainty or discomfort is manifested when interacting with individuals with intellectual disabilities.